Assessing Vulnerability and Resilience to Climate-Induced Saltwater Intrusion of Smallholder Vegetable Farmers in The Gambia - Saidy, Alieu; Diallo, Yacouba; Jaiteh, Malanding; Yessoufou, Adjani Nourou-Dine; Kargbo, Alpha; Jaiteh, Bubacarr (Journal of Agricultural Studies, 2025)
Saltwater intrusion represents an increasingly significant challenge for smallholder vegetable farmers in The Gambia, particularly in the Lower River Region (LRR) and North Bank Region (NBR). This study therefore examines the demographic, vulnerability of agricultural landscape to saltwater intrusion, and the resilience of 35 smallholder vegetable farming households in the North Bank (NBR) and Lower River (LRR) regions, using the Composite Index of Climate Resilience (CICR) specific to saltwater intrusion and the Resilience Index Measurement and Analysis (RIMA) framework. Given that 91% of households derive their livelihoods from agricultural production, the study identifies high levels of awareness regarding climate change (94%) and indicate that 89% of farmers have experienced a decline in crop yields and income as a result of saltwater intrusion. There are regional and gender differences, the NBR exhibits a higher Resilience Capacity Index (RCI) than the LRR. While female-headed households demonstrate greater access to essential services, yet face more significant barriers to agricultural assets. In contrast, male-headed households exhibit stronger adaptive capacities. In sum, the findings indicate that saltwater intrusion exacerbates vulnerabilities and threatens food security. This highlights the necessity for targeted, region-specific, and gender-sensitive interventions, including improved agricultural inputs, social safety nets, and literacy support, to strengthen resilience among Gambian smallholder farmers and support sustainable livelihoods.